2007
DOI: 10.1007/bf03033991
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of maxillofacial tumor withl-3-[18F]-fluoro-α-methyltyrosine (FMT) PET: a comparative study with FDG-PET

Abstract: Differential diagnosis of FMT-PET based on the uptake in maxillofacial tumors is equivalent to FDG-PET. However, the contrast of FMT uptake between maxillofacial tumors and the surrounding normal structures is higher than that of FDG, indicating the possibility of accurate diagnosis of maxillofacial tumors by FMT-PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…2-76 Br-BAMP provided the visualization of tumorous lesions more clearly than did 18 F-FAMT, indicating the high potential of 2-76 Br-BAMP as a new tumor imaging PET probe. Although human studies are needed, 2-76 Br-BAMP may detect various tumors such as lung and brain tumors, lymphomas, melanomas, and maxillofacial tumors as well as 18 F-FAMT does (24)(25)(26)(27). In addition to the relatively long halflife of 76 Br, 2-76 Br-BAMP exhibited slower elimination rates from the tumor than from the kidney, and thus a delayed-phase scan may visualize the tumor even if it is in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…2-76 Br-BAMP provided the visualization of tumorous lesions more clearly than did 18 F-FAMT, indicating the high potential of 2-76 Br-BAMP as a new tumor imaging PET probe. Although human studies are needed, 2-76 Br-BAMP may detect various tumors such as lung and brain tumors, lymphomas, melanomas, and maxillofacial tumors as well as 18 F-FAMT does (24)(25)(26)(27). In addition to the relatively long halflife of 76 Br, 2-76 Br-BAMP exhibited slower elimination rates from the tumor than from the kidney, and thus a delayed-phase scan may visualize the tumor even if it is in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of L-type amino acid transporter 1 as a therapeutic target in oral cancer has been described long before (34,35). We designed 18 F-FAMT as a specific PET radiotracer for L-type amino acid transporter 1 that is overexpressed exclusively in malignant tumors (12) and performed several clinical trials in comparison with 18 F-FDG in oral malignancies (10,14,19). Therefore, analysis of 18 F-FAMT and its corresponding tumor pathologic characteristics is fundamental for the development of a PET imaging-based comprehensive diagnosis of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…With a predetermined pathologically confirmed cutoff SUV of 3.0 for 18 F-FDG and 1.4 for 18 F-FAMT from previous PET study of maxillofacial tumors (19), PET volume computerized-assisted reporting performs autosegmentation to the threshold-defined volumes and automatically calculates MTV and average SUV (10). TLG of 18 F-FDG was calculated by multiplying MTV with the average SUV within that volume.…”
Section: Radiopharmaceuticals and Pet Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies with small numbers of patients have suggested that FMT is superior to FDG for the detection of musculoskeletal tumors, similar to FDG for the detection of head and neck tumors, and is superior to FDG for determining treatment response in lung cancer. 109,110 Conversely, small clinical studies that used FET indicated that it was generally worse than FDG for the detection of many tumor types, including head and neck cancer. 111,112 FET-PET did exhibit better specificity in several of the studies, raising the possibility that it may be better at differentiating tumor from inflammatory tissue.…”
Section: Imaging Protein and Cell Membrane Metabolismmentioning
confidence: 99%